Mental toughness in sport: Motivational antecedents and associations with performance and psychological health - Mahoney, J.; Gucciardi, Daniel; Ntoumanis, N.; Mallett, C. (Human Kinetics, 2014)
We argue that basic psychological needs theory (BPNT) offers impetus to the value of mental toughness as a mechanism for optimizing human functioning. We hypothesized that psychological needs satisfaction (thwarting) would be associated with higher (lower) levels of mental toughness, positive affect, and performance and lower (higher) levels of negative affect. We also expected that mental toughness would be associated with higher levels of positive affect and performance and lower levels of negative affect. Further, we predicted that coaching environments would be related to mental toughness indirectly through psychological needs and those psychological needs would indirectly relate with performance and affect through mental toughness. Adolescent cross-country runners (136 male and 85 female, Mage = 14.36) completed questionnaires pertaining to BPNT variables, mental toughness, and affect. Race times were also collected. Our findings supported our hypotheses. We concluded that BPNT is generative in understanding some of the antecedents and consequences of mental toughness and is a novel framework useful for understanding mental toughness.